PENGUATAN KETAHANAN KEUANGAN LEMBAGA DAN EKONOMI KELOMPOK TRANSPUAN DI KOTA SURABAYA - Nugroho, Robertus Adi; Angelina, Helen; Harefa, Mei Kristiani (Jurnal Abdimas Musi Charitas, 2025)
Purpose: This community service program was conducted in collaboration with Perwakos, a transgender organization in Surabaya, to strengthen economic resilience and institutional capacity. The program aimed to equip participants with digital skills focused on online business and video content creation as marketing strategies. Design/Methodology/Approach: The program began with a needs assessment through initial discussions, followed by structured training on online business, video production techniques, and digital marketing. Hands-on practice accompanied each session. Evaluation methods included pre-tests, post-tests, and assessment of participants’ video projects. Findings: Participants demonstrated notable improvement in digital skills, particularly in creating market-oriented video content. The program also contributed to the development of the Perwakos core team and facilitated network-building with external stakeholders. Practical Implications: The outcomes of this program support the transition of marginalized communities from reliance on informal sectors toward sustainable entrepreneurship. The program also provided practical tools and motivational support to overcome technological and attitudinal barriers. Originality/Value: This initiative presents an inclusive model of digital-based economic empowerment tailored for transgender communities. The integration of skill-building, mindset transformation, and support infrastructure offers long-term value for reducing social stigma and enhancing self-reliance.